2017
DOI: 10.1142/s0219467817500103
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Telegraph Diffusion Equation for Noise Reduction on Images

Abstract: The Telegraph Diffusion Equation (TDE) used in some noise reduction processes in an image includes two main parameters: the damping coefficient and the relaxation time. Classically, the first is determined globally for a given input image, while the second one is set constant. In this paper, we propose to determine the values of these parameters according to the information and the image local structure. We then get an adaptive diffusion equation that permits to better control the degree of smoothness and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…11 a and b show the PSNR of the images of Lena and bridge on which were applied different standard deviation of the noise (10, 20, 30) in function different values of λ. This technique for determining λ is commonly used in [9, 10]. The selected value λ=10.…”
Section: Experiences and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 a and b show the PSNR of the images of Lena and bridge on which were applied different standard deviation of the noise (10, 20, 30) in function different values of λ. This technique for determining λ is commonly used in [9, 10]. The selected value λ=10.…”
Section: Experiences and Resultsmentioning
confidence: 99%
“…The main limitation of their method is the calculation time of the bilateral filter and the choice of the damping coefficient in the TDE which does not depend on the image features. Ghislain et al [10] proposed the adaptation of TDE (A‐TDE). They showed that the damping coefficient and the relaxation time depend on the image features.…”
Section: Introductionmentioning
confidence: 99%
“…In the eigenface method, decoding is done by calculating the eigenvector and then represented in a large matrix [2]. This matrix has a feature value that serves to assess how close to a comparable object.…”
Section: Introductionmentioning
confidence: 99%